Perception of Nephrology residency training in Peru - Percy Herrera-Añazco; A.C. Rivas-Nieto; Vicente A. Benites-Zapata; Muñoz-del Carpio-Toia Agueda; Gomez Martin (Educación Médica, 2024)
Introduction: In the assessment of the second specialty training programs, the opinion of residents and graduates is essential to know the degree of satisfaction with the training received. The aimed was to assess the perceptions of Peruvian nephrology residents and graduates regarding their training. Material: A descriptive, cross-sectional study included all final-year residents and graduates of the nephrology program in 2022. An anonymous virtual survey assessed sociodemographic aspects, nephrology tutoring, clinical training, external rotations, research, the impact of the COVID-19 pandemic, and overall perception of their training. Results: With a response rate of 79.68%, 51 participants were evaluated. 76.48% of the participants rated their overall training during the residency as good. 58% agreed or strongly agreed that their tutor's performance was good. 66.6% agreed or strongly agreed that their theoretical training was good, with less certainty in genetic kidney diseases. 90% agreed or strongly agreed that their practical training was good, with less certainty in training in slow therapies, renal biopsies, acute peritoneal dialysis, and peritoneal dialysis catheter placement. 80.4% agreed or strongly agreed that the pandemic affected their training. The general perception had a positive correlation with the tutor's performance as good (r=0.50; P<.001), the good perception of the hospital's research level (r=0.47, P<.001), and the perception of good opportunities to get a job as a nephrologist (r=0.67, P<.001). Conclusion: Although, in general, the perception is positive, there are aspects in which the training of Peruvian nephrology residents should be improved. Resumen: Introducción: En la valoración de los programas formativos de segunda especialidad, la opinión de los residentes y egresados es fundamental para conocer el grado de satisfacción con la formación recibida. El objetivo fue evaluar las percepciones de los residentes y egresados de nefrología peruanos sobre su formación. Métodos: Estudio descriptivo transversal que incluyó a todos los residentes de último año y egresados de la carrera de nefrología en el año 2022. Mediante encuesta virtual anónima se evaluaron aspectos sociodemográficos, tutorías de nefrología, formación clínica, rotaciones externas, investigación, impacto del COVID-19 pandemia, y la percepción general de su formación. Resultados: Con una tasa de respuesta del 79,68%, se evaluaron 51 participantes. El 76,48% de los participantes calificaron como buena su formación global durante la residencia. El 58% estuvo de acuerdo o muy de acuerdo en que el desempeño de su tutor fue bueno. El 66,6% estuvo de acuerdo o muy de acuerdo en que su formación teórica fue buena, con menor certeza en enfermedades renales genéticas. El 90% estuvo de acuerdo o muy de acuerdo en que su formación práctica fue buena, con menor certeza en la formación en terapias lentas, biopsias renales, diálisis peritoneal aguda y colocación de catéter de diálisis peritoneal. El 80,4% estuvo de acuerdo o muy de acuerdo en que la pandemia afectó su formación. Conclusión: Si bien, en general, la percepción es positiva, existen aspectos en los que se debe mejorar la formación de los residentes de nefrología peruanos.